Theory of phase transitions in ferroelectric superlattices / Lim Kok Geng - Lim, Kok Geng (2015)
Ferroelectric superlattices comprising two or more different layers are currently a topic of active research because of their potential applications in memories and fundamental scientific interest. A thermodynamic model based on the Landau-Ginzburg theory is proposed to study the phase transitions in ferroelectric superlattices. An interface energy term is introduced in the free energy to describe the formation of intermixed layer with properties different from those of both layers. These intermixed layers are mutually coupled through the local polarization at interfaces. The effects of electrostatic coupling and interface intermixing on the internal electric field and polarization of superlattices which composed of alternate layers of ferroelectrics and paraelectrics are discussed. As an illustration, the model is applied to a superlattice consisting of a ferroelectric layer as PbTiO3 (PT) and a paraelectric layer as SrTiO3 (ST) on a ST substrate. Appropriate electrostatic boundary conditions are considered for the case of superlattice with polarization perpendicular to the surface or interface. The effect of interface intermixing and modulation period on the internal electric field and polarization are studied by changing the volume fraction or thickness ratio of the PT/ST superlattice. In addition, the spatially-varying internal electric field, dielectric susceptibility and polarization of these ferroelectric superlattices are calculated. Effects of modulation period and temperature on the internal electric field, dielectric susceptibility and polarization of these superlattices with inhomogeneous properties are examined. The polarization reversal in PT/ST superlattices with “switchable” polarization in intermixed layers is also studied. The dependence of polarization and internal electric field on an applied electric field is discussed. The polarization and internal electric field profiles at certain applied electric field are examined. Besides that, the effects of alternating interface charges, s of the ferroelectric superlattices are studied by taking into account the intermixing at the iii interfaces between layers. The alternating interface charges enhance the polarization of ferroelectric superlattices, and lead to the formation of an effective internal electric field in the superlattices. Lastly, the thermodynamic model is extended to study the effect of composition and interface intermixing on ferroelectric properties of BaTiO3=BaxSr1